Alternative wood fiber, biochar, and composted green waste growing media formulations for glasshouse strawberry (Fragaria X ananassa) production over two production cycles - Tumbure, Akinson; Corbett, Eoghan; Gaffney, Michael T. (Frontiers in Horticulture, 2025)
IntroductionThe exploration of local resources as growing media alternatives to peat and coir for soft fruit production is essential to improve self-sufficiency and environmental sustainability.MethodsThe agronomic performance of novel formulations of wood fiber plus 20%/40% biochar (3 types), 50% composted green waste (2 types), 50% bark (2 types), and 20% quarry filter-cake (1 type) were compared with coir, peat and rockwool. The two cropping cycle strawberry experiment involved re-use of growing media and replanting with new strawberry plants in the second year.ResultsFor both production cycles, there were no statistical differences between class 1, class 2, and total marketable berry yields per plant between the various growing media. A similar trend was observed for berry count per plant, biomass and chlorophyll content. However, in the first production cycle, a 50% composted green waste mix, a 20% quarry filter-cake mix, and a 40% biochar mix produced significantly smaller berries than coir. The same 20% quarry filter-cake mix also produced strawberry above-ground biomass with significantly less phosphorus (P) content than the coir control, while the same 40% biochar mix produced biomass with significantly less calcium (Ca) content than coir.DiscussionResults reveal that wood fiber containing alternative growing media has good potential for commercial use and minor adaptations are needed. However, these present complex relationships in the root zone that not only affect irrigation regimes and water uptake but also nutrient uptake. The differences in the materials were evident even when the growing media are fertigated with the same nutrient solution and fertigation frequency. Further studies on optimization of alternative growing media through altering irrigation frequencies and fertigation solutions are required.